An Epidemiological Study: Assessment of Symptomatic Osteoarthritis and its management in general population of Karachi with joint pain - Khan, Aisal; Syed Muhammad Mustahsan; Eraj, Quratulain; Parvez, Hina; Anwar, Ayesha; Ali, Munazza; Iqbal , Sameen; Urooj Fatima; Warsi, Aiman; Moeen, Tayyabah; Dastagir, Sundas; Tariq, Fateeha; et al. (International Journal of Endorsing Health Science Research, 2016)
Objective: To determine the frequency of symptomatic osteoarthritis in general population of Karachi presenting with joint pain. Introduction: People easily get tired due to heavy duty occupations to keep pace with the society. Arthralgia commonly called as “Joint pain” is one of the most frequently observed complain, especially in individuals aged 50 above. Methods: A cross-sectional study was conducted at Jinnah Postgraduate Medical Centre (JPMC) from 1st November 2013 to 25th November 2013. The data was collected from 316 patients presenting to the department of rheumatology and orthopedics with joint pain. A structured questionnaire was designed based on the clinical symptomatology of osteoarthritis. It was administered to the participants aged above 18 yrs. old. 17.7% of males and 82.3% of females participated in the study. Result: Out of 316 patients with joint pain, 71.2% (n=225) were diagnosed osteoarthritis on the basis of symptoms present with a high prevalence in females than males. The most common joints to be involved in osteoarthritis were found to be knee joint (90.2%) and hip joint (55.7%). The majority of the patients (n=109) had an X-ray of their joint and n=125 was getting analgesics as an effective therapy for osteoarthritis. Conclusion: The frequency of osteoarthritis is increasing in Karachi with globalization due to high level occupational stress along with recreational activity stress and other contributive factors. Female predominance as compare to that of man is quite alarming that needs to be controlled for maintaining future quality of life and providing ease for daily activities.